KREATIVITAS BERMAIN ANAK USIA DINI - Sari, Ratih Permata (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2019)
Creativity is one of the natural potential in children that must be developed optimally. Creativity itself is grown in the right brain, the brain that has the specification of thinking, processing data about feelings, emotions, art and music. All children born in the world must have a side of creativity, but in different levels. The low level of child creativity is influenced by two things: genetic factors (congenital birth) and environmental factors. This creativity will grow optimally if both factors are well integrated. Children's creativity will be able to be nurtured through play activities so that the child will be a creative and innovative person. Creativity will lead to the development of children's potential. For this reason children's creativity is important to be stimulated through various activities that children love. In essence, early childhood is at play time. So, teachers, parents and other adults should participate more with children through play activities. Facilitate children with various media to play so that children explore more and find new things by themself.